2004
DOI: 10.1063/1.1803103
|View full text |Cite
|
Sign up to set email alerts
|

Cyclostationary shot noise in mesoscopic measurements

Abstract: We discuss theoretically a setup where a time-dependent current consisting of a DC bias and two sinusoidal harmonics is driven through a sample. If the sample exhibits current-dependent shot noise, the down-converted noise power spectrum varies depending on the local-oscillator phase of the mixer. The theory of this phase-dependent noise is applied to discuss the measurement of the radio-frequency single-electron transistor. We also show that this effect can be used to measure the shot noise accurately even in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[20][21][22][23], a frequency domain description of the shot noise of time-varying signals revealed that spectral correlations explained a reduction in the sensitivity of some gravitational wave detectors. Timevarying shot noise models for vacuum tubes and junction diodes have also been developed [24][25][26][27], where again there are deviations from the standard, stationary shot noise model.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23], a frequency domain description of the shot noise of time-varying signals revealed that spectral correlations explained a reduction in the sensitivity of some gravitational wave detectors. Timevarying shot noise models for vacuum tubes and junction diodes have also been developed [24][25][26][27], where again there are deviations from the standard, stationary shot noise model.…”
Section: Introductionmentioning
confidence: 99%